贸易和发展 2018 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2019)
This flagship publication examines different aspects of the nature and role of international trade in the era of hyperglobalization and considers related policy challenges that will need to be addressed if trade is to contribute to a more stable and inclusive global economic order. Research provides authoritative data and analysis on trade, investment, finance and technology. UNCTAD offers solutions to the major challenges facing developing countries, particularly the poorest and most vulnerable nations. Beyond tailored analysis and policy recommendations, UNCTAD research also generates global standards that govern responsible sovereign lending and borrowing, investment, entrepreneurship, competition and consumer protection and trade rules.